A systematic review of transferable solution options for the environmental impacts of tidal lagoons. (January 2019) - Elliott, Kathryn; Smith, Helen C.M.; Moore, Fran; van der Weijde, Adriaan H.; Lazakis, Iraklis
Abstract: Tidal lagoons are presented as an environmentally friendly alternative to tidal barrages. This does not mean that their environmental impacts can be overlooked. A UK government review recommended a pilot scheme lagoon go ahead, with careful environmental monitoring. Despite recent government rejection of a lagoon scheme, it is still more important than ever to consider environmental solution options for any future lagoon developments. There are no operating lagoons in the world and so their environmental impacts are not fully understood. However, there is a vast quantity of literature available from other industries addressing similar impacts in the coastal, ocean and river environments. This systematic review follows the PRISMA and CEE guidance. Using this methodology the available literature covering relevant solution options from other industries that could be applied to future lagoon developments was quantified. This presents an investigation into solution options only, giving a quantitative analysis of what resources are available, how this compares to industry understanding, where the expertise lies globally, what impacts are being addressed and how applicable the solutions are for lagoon application. This paper analyses the extent and relevance of this available research on solutions as a resource for the nascent lagoon industry. Over half of the solutions found in this review require only small shifts in development for them to be realistic solution options for the lagoon industry in the future. This review opens the door on a vast and valuable resource and justifies the need for further investigation into solutions for the lagoon industry. Highlights: Recent advancements mean it is now more important than ever to consider management of the environmental impacts of tidal lagoons With no operational tidal lagoons in the world, there is no lagoon specific data or guidance on environmental solution options This review uses the PRISMA reporting and Collaboration on Environmental Evidence guidance to present 77 relevant papers documenting solution options from other relevant industries which could be applied to the environmental impacts of tidal lagoons Half of the solutions found in the literature require only small shifts in their development and adaption to be realistic solution options for the environmental impacts of tidal lagoons in the near future This review quantifies a valuable literature resource on available solution options from other industries which warrants further investigation for application in the lagoon industry.